2011
DOI: 10.1120/jacmp.v12i3.3480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the vaginal applicator and dummy pellets on the dosimetry parameters of Cs‐137 brachytherapy source

Abstract: In this study, dose rate distribution around a spherical 137Cs pellet source, from a low‐dose‐rate (LDR) Selectron remote afterloading system used in gynecological brachytherapy, has been determined using experimental and Monte Carlo simulation techniques. Monte Carlo simulations were performed using MCNP4C code, for a single pellet source in water medium and Plexiglas, and measurements were performed in Plexiglas phantom material using LiF TLD chips. Absolute dose rate distribution and the dosimetric paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Cesium sources were widely used in low-dose gynecological implants such as cylinder, tandem, and ovoid implants. Cs-137 sources are used in low-dose afterloading devices [10].…”
Section: High-energy Sourcesmentioning
confidence: 99%
“…Cesium sources were widely used in low-dose gynecological implants such as cylinder, tandem, and ovoid implants. Cs-137 sources are used in low-dose afterloading devices [10].…”
Section: High-energy Sourcesmentioning
confidence: 99%
“…Pelszynski et al (8,9) reported that the minimum possible radiation dose of only 25 Gy is necessary for lymphocytes to be efficiently inactivated in red blood cell units. Also, Anderson et al (10,11) mentioned that gamma irradiation is the only process that effectively prevents transfusion associated GVHD and suggested that blood components and products be irradiated to the lowest recommended dose (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) Gy) capable of preventing lymphocyte proliferation before blood transfusions. Nuclear radioactive sources like Cs-137 are used to deliver doses to blood products, and errors in calculating the radioactive decay of the radiation source (7) should be considered as a physical factor influencing the dose delivered to the blood product.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, this system contains some non-active pellets as a dummy, with the same dimensions and chemical composition as the active pellets. 6 Liu et al have published the TG-43 recommended dosimetric characteristics of the sources in this system. 12 In this study, from a set of 8 pellets, numbers 2-7 are considered active, and the remainders are non-active, in order to deliver 1.5 Gy of dose to 0.5 cm distance from the lateral surface of ovoids within 1.01 h.…”
Section: Selectron Ldr Systemmentioning
confidence: 99%